Natura 2000 experiences in Southeast Europe - Šobot, Aleksandar (Journal of comparative politics, 2020)
The main research objective is to determine the impact of Europeanisation on the nature protection system in the countries of Southeast Europe. Europeanisation is presented in the research through legislative and institutional changes due to the adoption of the European ecological network - Natura 2000. Comparative analyses were made in Slovenia, Croatia and Bosnia and Herzegovina. Data collection was primarily done through participant interviews in the establishment of Natura 2000 and secondary through all available relevant literature. After that, a policy analysis was carried out through a thesis and subthesis based on the maingoal. The conclusion was presented as a confirmation of the main thesis that Europeanisation led to changes in Southeastern Europe's nature protection system.
Keywords: Comparative analysis; Environmental protection; Europeanization; Evropeizacija; Natura 2000; Primerjalna analiza; Varstvo okolja